Peran Kurikulum Merdeka dalam Meningkatkan Mutu Pendidikan di Sekolah Dasar - Erna Zumrotun; Efa Widyastuti; Sutama Sutama; Anam Sutopo; Budi Murtiyasa (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Kurikulum Merdeka has become one of the government’s programs in an effort to develop the quality of education by giving schools the freedom to develop content, methods, models, and learning assessments in accordance with the characteristics of the local environment, culture, and issues around, as well as student potential. This study aims to examine the role of the Kurikulum Merdeka improving the quality of education in primary schools. The subject of this study is SDN 8 Suwawal where the school is one of the primary schools in Jepara that has implemented the Independent Curriculum in the 2022/2023 academic year. The research method used is a qualitative research type case study. The research design used is using data collection techniques through observation, interviews, and documentation. The results of the study show that the implementation of the Kurikulum Merdeka has a positive impact on improving the quality of education in primary schools, including: increasing student motivation to learn, developing creativity and 21st-century skills, strengthening character and national values in accordance with the 6 dimensions of Pancasila, and increasing teacher independence and professionalism.